Effects of Green Tea on Serum Iron Parameters and Antioxidant Status in Patients with β-Thalassemia Major - Ehsan Soeizi, Maryam Rafraf, Mohammad Asghari-Jafarabadi, Aida Ghaffari, Azim Rezamand, Farideh Doostan (Tabriz University of Medical Sciences, 2017)
Background: Iron overload and accelerated oxidative stress are main factors in the pathogenesis of β-thalassemia major. The objectives of this study were to examine the effects of green tea consumption on serum iron, ferritin and transferrin saturation (TS) and antioxidant status in β-thalassemia patients. Methods: This study conducted on 52 subjects with β-thalassemia major (males and females) ≥18 y. The intervention group (n= 26) consumed green tea (2.5 g /150 mL hot water) 3 times per day for 8 wk and the control group (n= 26) followed a water regimen. Anthropometric measurements, blood samples and 24-h dietary recalls were gathered at the baseline and at the end of the trial. Independent t test, paired t test and analysis of covariance were used for data analysis. Results: Mean of serum iron, ferritin, malondialdehyde (MDA) and total antioxidant capacity (TAC) were 234.7±49.3 μg/dL, 2776.07±533.4 ng/dl, 3.01±0.64 nmol/ml and 2.2665±0.77 nmol/l in green tea group and 298.19±66.87 μg/dL, 3070.23±643.6 ng/dl, 298.19±66.87 nmol/ml and 2.0862 ±0.35 nmol/l in control group at baseline, respectively. Green tea significantly decreased serum levels of iron, ferritin and MDA and increased TAC compared with control group (all, P < 0.05). No significant changes were seen in TS value in both groups. Conclusions: Green tea consumption had favorable effects on iron status and oxidative stress in studied subjects and may be useful in management of these risk factors in patients with β-thalassemia major.